Historic native peoples of Texas - Foster, William C., 1928- (University of Texas Press, 2008)
Several hundred tribes of Native Americans were living within or hunting and trading across the present-day borders of Texas when Cabeza de Vaca and his shipwrecked companions washed up on a Gulf Coast beach in 1528. Over the next two centuries, as Spanish and French expeditions explored the state, they recorded detailed information about the locations and lifeways of Texas's Native peoples. Using recent translations of these expedition diaries and journals, along with discoveries from ongoing archaeological investigations, William C. Foster here assembles the most complete account ever published of Texas's Native peoples during hte early historic period (AD 1528-1722).